Diabetic Gastroparesis: Perspectives From a Patient and Health Care Providers - Adam D. Farmer; Caroline Bruckner-Holt; Susanne Schwartz; Emma Sadler; Sri Kadirkamanthan (Journal of Patient-Centered Research and Reviews, 2019)
Gastroparesis is defined as a delay in gastric emptying in the absence of mechanical obstruction in the stomach. Gastroparesis has a number of causes, including postsurgical, secondary to medications, postinfectious, idiopathic, and as a complication of diabetes mellitus, where it is underrecognized. The cardinal symptoms of diabetic gastroparesis are nausea, early satiety, bloating, and vomiting. Diabetic gastroparesis is more common in females and has a cumulative incidence of 5% in type 1 diabetes and 1% in type 2 diabetes. It is associated with a reduction in quality of life and exerts a significant burden on health care resources. The pathophysiology of this disorder is incompletely understood. Diagnosis is made based on typical symptoms associated with the demonstration of delayed gastric emptying in the absence of gastric outlet obstruction. Gastric emptying scintigraphy is the gold standard for demonstrating delayed gastric emptying, but other methods exist including breath testing and the wireless motility capsule. Diabetic gastroparesis should be managed within a specialist multidisciplinary team, and general aspects involve dietary manipulations/nutritional support, pharmacological therapy, and surgical/endoscopic interventions. Specific pharmacological therapies include prokinetics and antiemetics, with several new medications in the drug development pipeline. Surgical/endoscopic interventions include botulinum toxin injection into the pylorus, gastric peroral endoscopic myotomy and gastric electrical stimulation. This article provides a detailed review and summary of the epidemiology, pathophysiology, investigation, and management of diabetic gastroparesis, and also gives an individual patient’s perspective of living with this disabling disorder.